Akibat Hukum Terhadap Keabsahan Akta Pejabat Pembuat Akta Tanah Yang Mengurangi Nilai Jual Tanah Aset Desa Berdasarkan Harga Nilai Jual Objek Pajak (Studi Putusan Nomor 194/Pid.Sus/TPK/2014/Pn.SBY) - Faisal Imam Harahap; Ahmad Fauzi; Masitah Pohan (Iuris Studia: Jurnal Kajian Hukum, 2020)
Actions to reduce the actual selling price included in the deed made before the Land Deed Officer are carried out by the parties in the sale and purchase deed as a form of avoidance of the value of buying and selling tax on land, by avoidance by reducing the actual sale price of land in the sale deed buying will certainly hurt the country's economy. There were also violations in the implementation of land sale and purchase contained in this decision, where it was supposed to be made in the form of land asset deed in the presence of a Land Deed Officer, namely in making an asset sale deed, or exchange of village land assets based on Law Number 6 of 2014 concerning Villages, and Article 32 of the Minister of Home Affairs Regulation Number 1 of 2016 concerning Management of Village Assets, but the parties and Officials of Land Deed in this case do not implement this provision. The problems raised in this study are how the provisions and legal rules for making village asset sale deeds in the form of land in the presence of Land Deed Officials, legal protection for buyers of village asset sale deeds in the form of land where there is a reduction in land sale value of village assets based on the object tax selling value, and the legal consequences of the village asset sale deed in the form of land in which there is a reduction in the land sale value of the village asset based on the selling value of the tax object